Endocrown restorations for extensively damaged posterior teeth: clinical performance of three cases - Konstantinos Tzimas; Maria Tsiafitsa; Paris Gerasimou; Effrosyni Tsitrou (Restorative Dentistry & Endodontics, 2018)
The restoration of endodontically treated teeth (ETT) with more than one cusp missing and thin remaining walls is challenging for the general practitioner. The use of posts combined with full coverage restorations is a well-established approach, yet not following the minimal invasive principles of adhesive dentistry. Endocrowns are indirect monoblock restorations that use the pulp chamber of the ETT for retention. In this study the fabrication of 4 endocrowns and their clinical performance will be discussed. Two clinical cases include computer-aided design/computer-aided manufacturing manufactured molar endocrowns (one feldspathic ceramic and one hybrid composite-ceramic restoration) and the other two are dental laboratory manufactured resin composite premolar endocrown restorations. The modified United States Public Health Service criteria were used to assess the clinical behavior of the restorations at different follow up periods. Endocrown restorations present a satisfactory clinical alternative, either by the use of resin composite or glass ceramic and hybrid materials. Specific guidelines with minimal alterations should be followed for an endocrown restoration to be successful. Due to limited evidence regarding the long term evaluation of this restorative technique, a careful selection of cases should be applied.